Theology, Science, and Human Uniqueness: A Response to Wentzel van Huyssteen - Novak, David (Toronto journal of theology, 2010)
In challenging Wentzel van Huyssteen's theology of human uniqueness, it is argued first that theology is reflection on the meaning of revelation, which is the fundamental datum of a religion to which a theologian is personally committed. Whereas one's theology is a human construct, one's religion is not. Concerning the relation of theology and natural science, it is argued that each discipline can learn from the other without having to justify itself by the principles of the other, especially theology not having to justify itself by naturalist criteria (the error of "natural theology"). Concerning human uniqueness, it is argued that only a biblically based theology, with its doctrine of the imago Dei, can constitute a theory of human uniqueness that takes humans to be different from the rest of creation, yet not in opposition to it. Concerning the relation of Judaism and Christianity, it is argued that Jewish "traditionalism" or "particularism" is not a detriment Christianity has superseded, but a manifestation of the essential embodiment (both physical and political) of human being.